Participatory Rational Justice in Criminal Law Reform as an Integrative Theory for Substantive Justice and Social Legitimacy - Lesmana, CSA Teddy; Sulistiani, Lies; Putri, Nella Sumika; Dewi, Deshinta Arrova (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2026)
The traditional criminal justice system, predominantly grounded in retributive and legalistic paradigms, has increasingly struggled to respond to contemporary social realities, including prison overcrowding, limited victim participation, procedural rigidity, and declining public trust in legal institutions. In many jurisdictions, retributivism prioritizes punishment over social restoration, restorative justice mechanisms remain fragmented and marginal, and economic analysis of law (EAL) often emphasizes efficiency while overlooking normative legitimacy and participatory justice. Responding to these practical and conceptual limitations, this article proposes a new integrative framework Participatory Rational Justice (PRJ) which reconceptualizes criminal justice as a collaborative, community-engaged, and outcome-oriented process. Employing an interdisciplinary approach through theoretical analysis and comparative perspectives on criminal justice reforms, this study situates PRJ within existing reform practices that seek to balance efficiency, accountability, and social welfare. PRJ combines policy rationality, active stakeholder participation, resource efficiency, and social restoration to produce justice outcomes that extend beyond formal legality toward substantive societal benefits. By bridging procedural justice, economic legal reasoning, and capability-based substantive justice, PRJ offers a conceptually grounded yet practically relevant alternative for criminal justice reform. This study argues that adopting PRJ can enhance institutional legitimacy, optimize resource allocation, and foster a more inclusive legal culture, thereby contributing to the adaptive and sustainable development of contemporary criminal justice systems.